Submission System for Uninhabitable Houses of The Housing and Settlement Area Office - Zulfa, Ira; Eliyin, E; Yustisar, Muhamad; Septima, Richa Santy; Marlina, Seli (LPPM STIKOM Tunas Bangsa, 2024)
The swift progression of information technology has profoundly influenced diverse sectors such as government, private enterprises, and education. This research delves into the utilization of information technology within the housing sector, pinpointing the issues of inefficiency inherent in the conventional method of requesting uninhabitable homes in Aceh Tengah, Indonesia.The existing manual system employed by the Aceh Tengah Housing and Settlement Agency frequently leads to delays, loss of data, and inefficiencies. To address these shortcomings, this study suggests the creation of an online system that enhances the efficiency of the submission process. The goals of this study involve the digitization of the request submission process for uninhabitable residences, thereby increasing convenience for residents, Centralizing data storage to enhance data reliability and diminish the likelihood of loss or damage, and Improving both the accuracy and efficiency of data reporting and analysis. Through the introduction of an online platform, the Aceh Tengah Housing and Settlement Agency seeks to offer a service that is more efficient, transparent, and responsive to its residents, with the ultimate aim of enhancing the quality of housing and living conditions within the area.